PROBLEMATIKA PROSES REHABILITASI & REONSTRUKSI PASCA BENCANA MENGUNAKAN METODE PARTISIPATIF MASYARAKAT - Ira Modifa; Robert Tua Siregar; Rudi Salam Sinaga (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
In the handling of the 2004 Aceh Tsunami Disaster and the 2004 Nias Earthquake, many parties as providers of assistance used a community-based rehabilitation and reconstruction development model one of which is UN-HABITAT under the auspices of the United Nations, This study aims to find the most effective and fair participatory postmortem participatory development guidelines for disaster-affected communities through case studies of Aceh Nias Settlement Support Program (ANSSP) 2005-2007. Analytical descriptive methods are used to obtain data. Data collection techniques used literature study and documentation study. The results of the study found that participatory community-based development, especially post-disaster handling, has proven good results. The literature study, interview and ANSSP report book 2007 published by UN - Habitat, illustrates that the participatory development model is able to answer all negative factors.